20.2: Ultra‐Bright, Highly Efficient, Low Roll‐Off Inverted Quantum‐Dot Light Emitting Devices (QLEDs). Issue 1 (June 2015) - Dong, Yajie; Caruge, Jean‐Michel; Zhou, Zhaoqun; Hamilton, Charles; Popovic, Zoran; Ho, John; Stevenson, Matthew; Liu, Guo; Bulovic, Vladimir; Bawendi, Moungi; Kazlas, Peter T.; Steckel, Jonathan; et al.
Abstract : We report an ultra‐bright, highly efficient, low roll‐off, inverted quantum dot‐based red light emitting device (QLED) using solution‐processed zinc oxide nanoparticles and cesium carbonate films as the electron injection and hole blocking layers, respectively. Record luminance of 165, 000 Cd/m 2 has been obtained at a current density of 1000 mA/cm 2 with a low driving voltage of 5.8 V for deep red device with CIE coordinates of (0.69, 0.31).